Chronicle - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1997)
1. 102nd AES Convention, Munich, 22-25 March 1997; 2. 1997 IEEE International Ultrasonic Symposium, October 5-8, 1997, Toronto Marriot Eaton Centre Toronto, Ontario, Canada, Sponsored by the Ultrasonics, Ferroelectrics and Frequency Control Society; 3. 7-th Spring School on Acousto-Optics and Applications, 18-22 May, 1998 Gdańsk, The School is organized by University of Gdańsk, Institute of Experimental Physics in co-operation with the Quantum Molecular Acoustics and Sonochemistry; 4. Joint Meeting of the 16-th International Congress on Acoustics and the Acoustical Society of America, Seattle, Washington, USA, 20-28 June 1998.